2015
DOI: 10.1007/s00432-015-1910-9
|View full text |Cite
|
Sign up to set email alerts
|

Should KRAS mutation still be used as a routine predictor of response to EGFR-TKIs in advanced non-small-cell lung cancer? A revaluation based on meta-analysis

Abstract: In unselected advanced NSCLC patients, KRAS mutations could be used as a potential negative predictor of clinical benefit from EGFR-TKIs. However, KRAS testing is of limited value to identify patients for EGFR-TKIs when EGFR status is considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Resistance to EGFR-TKIs treatment for KRAS mutant NSCLC was also reported in other two meta-analysis conducted by Chen et al [ 56 ] and Min et al [ 57 ]. The reported pooled RR for ORR was 0.29 (95% CI 0.18-0.47) in Chen's study and 0.21 (95% CI 0.12-0.39) in ours while the reported pooled HR for PFS was 1.86 (95% CI 1.51-2.29) in Min's study and 1.46 (95% CI 1.23-1.74) in ours, showing highly consistent results among studies.…”
Section: Discussionsupporting
confidence: 68%
“…Resistance to EGFR-TKIs treatment for KRAS mutant NSCLC was also reported in other two meta-analysis conducted by Chen et al [ 56 ] and Min et al [ 57 ]. The reported pooled RR for ORR was 0.29 (95% CI 0.18-0.47) in Chen's study and 0.21 (95% CI 0.12-0.39) in ours while the reported pooled HR for PFS was 1.86 (95% CI 1.51-2.29) in Min's study and 1.46 (95% CI 1.23-1.74) in ours, showing highly consistent results among studies.…”
Section: Discussionsupporting
confidence: 68%
“…In the last two decades, many studies have been published analysing the prognostic and predictive roles of KRAS mutations in sustaining resistance to different types of treatment such as EGFR Tyrosine-Kinase Inhibitors (TKIs) and chemotherapy 15 16 17 . KRAS mutated patients were indicated to have a worse prognosis and resistance to treatment in different types of cancer but no clear conclusions have been stated for NSCLC 18 .…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Several prospective studies have shown that KRAS mutations predict poor survival and efficacy of EGFR-TKIs. 34 In addition, particular KRAS mutation subtypes may lead to different prognosis. Zer et al conducted a pooled analysis of 275 patients with KRAS mutation treated with EGFR-TKIs, which showed that patients with G12C/G12V mutation had a poor prognosis, while G12D/G12S positive patients could benefit from EGFR-TKIs.…”
Section: Kras Mutation As a Predictive Factormentioning
confidence: 99%